Boredom: a Political Issue - García Quesada, George I. (2020)
This chapter examines the concept of boredom in several philosophers in the line from German Idealism to Western and contemporary Marxism, relating the changes in this concept to successive social transformations. We thus propose a periodization for the conceptualization of boredom, which allows us to highlight the historicity of the concepts of boredom in philosophy and their inherent political (utopian) content. In this overview, we find two fundamental concepts of boredom: emptiness-boredom and repetition-boredom. These concepts are related to different treatments of boredom from these authors, oscillating between its praise as a long time for subjective introspection and its denunciation as a symptom of alienated time. Finally, we draw some considerations about time and boredom in contemporary societies.